Pemanfaatan Budgeting Dalam Manajemen Keuangan Untuk Meningkatkan Efektivitas Program Promosi Kesehatan Di Rumah Sakit Abcd - Ningsih Palupi, Hana Susila; Yuwono, Minto; Susilowati, Etty (Politeknik Raflesia Press, 2024)
This study aims to explore effective financial management strategies to support promotion programs or health programs at ABCD Hospital. By analyzing hospital financial data and conducting surveys and interviews with related staff, this research identifies inefficient spending patterns and evaluates their impact on the effectiveness of promotional programs in the healthcare industry. As a result of the research, the findings show that smarter financial management can increase the allocation of funds for more effective promotions, while also identifying areas where increased efficiency is needed. It is hoped that the results of this research will provide valuable insight for parties involved in hospital financial management, including administrators, financial managers and health practitioners. By implementing best practices in fund management, hospitals can increase the effectiveness of their health promotion programs, which in turn will contribute to improving overall community health